Synthesis and properties of polyurethane wood adhesives derived from crude glycerol-based polyols. (December 2017) - Cui, Shaoqing; Luo, Xiaolan; Li, Yebo
Abstract: Crude glycerol, a waste stream of the biodiesel production process, is low-cost renewable feedstock for the production of chemicals and polymers. In this study, polyurethane (PU) adhesives were synthesized from crude glycerol-based polyols (CG-based polyols) for wood bonding applications. Effects of different variables, including hydroxyl values of CG-based polyols, chain extenders, and the molar ratio of NCO/OH on the properties of PU adhesives were investigated. The chemical structures of PU adhesives were characterized, and their thermal, mechanical, and chemical resistance properties were evaluated. The experimental results indicated that an increase of the NCO/OH molar ratio (1.3) substantially improved bonding strength by up to 38 MPa. Higher thermal stability and stronger chemical resistance to hot and cold water and to alkali and acid solutions were observed comparing to vegetable oil-based adhesives. However, the effect of the hydroxyl value of polyols on bonding strength was not significant. Additionally, bond strength of crude glycerol-based PU adhesives was comparable to that of some commercial PU wood adhesives. All these properties demonstrated the potential of CG for PU wood adhesive applications, particularly for fast-curing uses.